Meningkatan Kemampuan Berbicara Melalui Metode Pembelajaran Simulasi Pada Siswa Kelas V - Dedeh Sumarni; Helmia Tasti Adri; Daningsih Daningsih; Anne Effanne; Erlina Erlina (THE JOER: Journal Of Education Research, 2022)
From the author's observations, it is known that the ability to speak Indonesian needs to be improved where this can be seen from several indications, including some students who are not able to use Indonesian properly and correctly in daily interactions with teachers, colleagues, parents and the community. The problems above are caused by the lack of learning strategies that can improve the ability to speak Indonesian, one of which is the less optimal provision of simulation methods in learning Indonesian. The author aims to conduct research on efforts to improve the ability to speak Indonesian through thesimulation learning method in fifth grade students of SD Negeri Sukahati 01, Citeureup District, Bogor Regency. One of the steps that are expected to improve the ability of students to speak Indonesian is to implement a simulation method in learning Indonesian. This research was carried out at SD Negeri Sukahati 01, Citeureup District, Bogor Regency with the time the research was carried out starting from July 2020 to December 2020. The research method used is a qualitative description method in the form of Classroom Action Research, namely the method used to describe, describe, and explain the symptoms ofresearch and strive to draw conclusions